Vesicular and plasma membrane glutamate transporters - Borghans, Bart; Dmitrieva, Natalia; Nikiforov, Aleksandr; Fahlke, Christoph (Frontiers in Biophysics, 2025)
Glutamate is the major excitatory neurotransmitter in the mammalian central nervous system. After exocytotic release from presynaptic nerve terminals, glutamate diffuses across the synaptic cleft and opens postsynaptic ionotropic glutamate receptors, thus depolarizing the postsynaptic neuron. Synaptic activity is terminated by rapid and efficient uptake into surrounding neurons and glial cells. The function of a glutamatergic synapse thus critically depends on two distinct transport systems: vesicular and plasma membrane glutamate transporters. Vesicular glutamate transporters (VGLUTs) accumulate glutamate in synaptic vesicles and determine the amount of released glutamate. Plasma membrane glutamate transporters (excitatory amino acid transporters, EAATs) clear the synaptic cleft from glutamate, setting the time resolution and energy demand of glutamatergic synaptic signaling. Both classes of glutamate transporters are not only secondary-active transporters, but also function as chloride channels, with different roles in chloride and glutamate homeostasis. Despite similar transport functions, VGLUTs and EAATs are structurally diverse and employ different molecular mechanisms to overcome the same chemical challenges. We here review recent progress in understanding the molecular and cellular biophysics of vesicular glutamate transporters and compare their properties with plasma membrane glutamate transporters.